Larvicidal Effects of Nanoliposomes Containing Clove and Cinnamon Essential Oils, Eugenol, and Cinnamaldehyde against the Main Malaria Vector, Anopheles stephensi Liston - Alireza Sanei-Dehkordi; Roghayeh Heiran; Ghazaal Roozitalab; Narges Elahi; Mahmoud Osanloo (Psyche: A Journal of Entomology)
The use of larvicides, especially in endemic regions, is recommended for malaria control. However, due to the excessive use of synthetic larvicides, resistance in mosquitoes and environmental pollution have been challenges. In the current study, nanoliposome containing clove and cinnamon essential oils and their major ingredients, i.e., eugenol and cinnamaldehyde, were first prepared; particle size and successful loading were investigated using DLS (Dynamic Light Scattering) and ATR-FTIR (Attenuated Total Reflection-Fourier Transform InfraRed) analysis. Larvicidal effects of the nanoliposomes and nonformulated samples were then investigated against Anopheles stephensi. The best-observed efficacy (LC50 5.4 μg/mL) was related to nanoliposomes containing eugenol with a particle size of 109 ± 4 nm. However, LC50 values of the other three nanoformulations were also around 10 μg/mL; all four prepared nanoformulations were thus introduced as natural larvicides for further investigations in the field conditions.